Electrochemotherapy: a good idea in recurrent basal cell carcinoma treatment. (February 2015) - Ruggeri, Roberta; Maurichi, Andrea; Carla Tinti, Maria; Cadenelli, Pierfrancesco; Patuzzo, Roberto; Gallino, Gianfrancesco; Santinami, Mario
SUMMARY : Basal cell carcinoma (BCC) is the most common skin cancer in Caucasian population. Surgical excision is the gold standard treatment for BCC. Secondary surgical approach in patients presenting surgical scars after multiple surgical excisions or submitted to radiotherapy without obtaining a safe clearance margin, should be avoided. In recent years the use of electrochemotherapy (ECT) in head and neck cancers using intravenous bleomycin was specifically addressed and BCC resulted to be among tumors with the best response to ECT. We report a case of a recurrent nasal BCC treated with ECT with a complete regression of lesions after 8 weeks and a disease free period of 7 months. ECT is a good palliative treatment not affecting survival rate but improving quality of life in patients.